50 things to do with a penknife - Collins, Matt (Princeton Architectural Press, 2017)
"Whether you're a beginner or seasoned whittler, this practical guide to the age-old yet newly popular art of whittling will delight, inspire, and instruct you. Featuring projects that cater to a range of skill levels - including a slingshot, spoon, whistle, chopsticks, fish hook, bookmark, and more elaborate carvings like a star mobile - Fifty Things to Do with a Penknife is the perfect combination of cool craftsmanship with savvy survival-skill projects, accompanied by detailed step-by-step illustrations, making it ideal for the creative adventurer with a penknife in your life!" -- back cover.